2018
DOI: 10.1097/md.0000000000010236
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristic and risk factors of recurrent sexual abuse and delayed reported sexual abuse in childhood

Abstract: Child sexual abuse (CSA) is a global problem that affects children of all ages, and the evaluation of these victims by psychologic and gynecologic experts in pediatric emergency departments is an important issue. Few data are available on the characteristics of children admitted to pediatric emergency department with recurrent CSA and delayed reported CSA. The aim of the present study was to describe the clinical features of, and risk factors for, recurrent CSA and delayed reported CSA. The study retrospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 22 publications
(20 reference statements)
0
27
1
2
Order By: Relevance
“…However, in cases of pregnancy by incest, our finding of a higher prevalence of adolescent intimidation (yet due to their condition of vulnerability) diverged from other studies which point to both intimidation and psychological threats as the most frequent forms of coercion [28,29]. In addition, the adolescent’s age, when less than 14 years, configured as a form of vulnerability which was significantly more frequent in cases of incest, emphasizing family dynamics and the victim’s physical inability to offer resistance as critically related phenomenon.…”
Section: Discussioncontrasting
confidence: 87%
“…However, in cases of pregnancy by incest, our finding of a higher prevalence of adolescent intimidation (yet due to their condition of vulnerability) diverged from other studies which point to both intimidation and psychological threats as the most frequent forms of coercion [28,29]. In addition, the adolescent’s age, when less than 14 years, configured as a form of vulnerability which was significantly more frequent in cases of incest, emphasizing family dynamics and the victim’s physical inability to offer resistance as critically related phenomenon.…”
Section: Discussioncontrasting
confidence: 87%
“…However, an additional 328 studies were excluded because they did not meet the inclusion criteria for this review. This process left 79 individual studies eligible for inclusion 24 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 ,…”
Section: Resultsmentioning
confidence: 99%
“…The pooled ORs for each of the individual types of childhood maltreatment are presented in Table 1 (for forest plots, see eFigures 1-11 in the Supplement ). Sexual abuse was associated with 3.5-fold increased odds for suicide attempts (48 studies 24 , 34 , 37 , 38 , 40 , 41 , 43 , 44 , 46 , 47 , 49 , 50 , 51 , 52 , 53 , 55 , 56 , 57 , 61 , 62 , 63 , 64 , 68 , 73 , 74 , 76 , 77 , 81 , 82 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 93 , 94 , 95 , 97 , 100 , 101 , 102 , 103 , 104 , 106 , 108 , 111 ; OR, 3.42; 95% CI, 2.90-4.00; I 2 = 97.4%), but heterogeneity was high (funnel plots in eFigure 12 in the Supplement ). Physical abuse was associated with a 2-fold increase in the odds for suicide attempts (26 studies 34 , 37 , 40 ...…”
Section: Resultsmentioning
confidence: 99%
“…The extent of CSA recurrence during childhood is not well understood. One study noted rates as high as 35.4% in an National Child Abuse and Neglect Data System (NCANDS) cohort of 3,835 children with first confirmed CSA in 2002 (Sinanan, 2011), and another found that 35% of emergency department visits for CSA involved recurrence (Hu et al, 2018). This study also noted that recurrent CSA was associated with poor school performance and more psychiatric problems, attempted suicide, treatment with antipsychotic medication, and other comorbidities (Hu et al, 2018).…”
mentioning
confidence: 99%
“…One study noted rates as high as 35.4% in an National Child Abuse and Neglect Data System (NCANDS) cohort of 3,835 children with first confirmed CSA in 2002 (Sinanan, 2011), and another found that 35% of emergency department visits for CSA involved recurrence (Hu et al, 2018). This study also noted that recurrent CSA was associated with poor school performance and more psychiatric problems, attempted suicide, treatment with antipsychotic medication, and other comorbidities (Hu et al, 2018). When considering adolescent and adult revictimization, there are even higher rates of recurrence with reports ranging from 30% to 70% (Barnes, Noll, Putnam, & Trickett, 2009; Brenner & Ben-Amitay, 2015; Classen, Palesh, & Aggarwal, 2005).…”
mentioning
confidence: 99%